DRIVERS OF DEFORESTATION AND FOREST DEGRADATION IN NAMKADING NATIONAL PARK OF LAOS - Chanthavong, Bakham; Van Khoa, Phung; Thongmanivong, Sithong; Van Tu, Nguyen (Journal of Forestry Science and Technology, 2021)
Understanding the drivers of deforestation and forest degradation in the Namkading National Protected Area, Laos is important for introducing appropriate technique and policy interventions. Here, we applied GIS and satellite imagery to map deforestation and forest degradation areas in the reserve and identified the drivers and its driving factors by analyzing the local perceptions using questionnaire surveys, group discussions, and field observations. The results indicated that deforestation areas decreased by 61,98 hectares. And forest degradation area increased by 732,13 hectares between 2015 and 2019. We found direct drivers of forest deforestation and forest degradation in the protected area are unsustainable harvest of forest products, uncontrolled forest fire and agricultural expansion. The main indirect drivers are poverty, high demand of timber products in international markets, and ineffective law enforcement in Laos particularly in Borlikhamxay. Our analysis indicates that deforestation and forest degradation are caused by wood furniture producers, agricultural practitioners, charcoal makers, land migrants, firewood collectors, and subsistent farmers. Based on group discussions showed that some activities could be introduced to mitigate these drivers such as implementing the law enforcement related to forestry, selection of alternative income generation for local community live in and surrounding the Namkading National Protected Area along with the provision of environmental education to reduce the driving factors to deforestation and forest degradation and support the sustainable forest resource management of this protected area in the long-term.